Muscle patterning and specification in Drosophila. - Ruiz-Gomez, M. (International Journal of Developmental Biology, 1998)
There are obvious differences in the way sense organs and muscles are generated during Drosophila embryogenesis. For example, all the cells that compose the final sense organ are derived from a unique cell through a well-established lineage, whereas each muscle is formed by fusion of myoblasts that belong to two different populations: a founder cell and a pool of fusion competent cells. Despite these differences, similar genes and mechanisms appear to be involved in the generation of the pattern of sense organs and in muscle development. Thus, the process of specifying individual cells and endowing them with the ability to initiate neuronal or muscle development, as well as the acquisition of alternative fates among sibling cells, appear to be under similar genetic control both in neural and muscle development.